A STUDY IN SCARLET - Doyle, Arthur Conan, Sir, 1859-1930; Fitch, Kenneth W.; Moskowitz, Seymour (Newbury, Berkshire : CCS Books, 2016)
When a Scotland Yard detective asks for assistance, Sherlock Holmes uses his powers of rational, reasoned observation and deduction to solve a murder case. Then, in Adventure of the Speckled Band, Sherlock Holmes comes to the aid of a client whose sister's dying words referred to a mysterious speckled band.
Primary.
Keywords: Holmes, Sherlock -- (Fictitious character) -- Comic books, strips, etc; Private investigators -- England -- Comic books, strips, etc; Children's stories -- Comic books, strips, etc; Graphic novels; Comics adaptations